Radical Scavenging, Proteases Activities, and Phenolics Composition of Bark Extracts from 21 Medicinal Plants. (16th March 2015) - Asam Raza, Muhammad; Shahwar, Durre; Khan, Tania
Abstract : Stem barks derived from twenty-one medicinal plants were extracted in methanol (100%) and acetone-water (70 : 30 v/v) and at room as well as at reflux temperature conditions. Total phenolic contents, determined using FC (Folin Ciocalteu) reagent, ranged from 528 to 715 mg GAE/g of crude extract. 15 out of 21 plants showed DPPH activity more than 90% and the rest of plants exhibited the activity in the range of 87–89%. The methanolic extract of P. granatum obtained at room temperature showed the highest antiradical activity (96%). The extracts with similar % radical scavenging of DPPH ∙ showed significant variation in EC50 value. Radical scavenging activity of E. rostrata, M. champaca, A. modesta, P. roxburghii, P. longifolia, E. suberosa, and F. infectoria was evaluated for the first time. A strong correlation between total phenols and antiradical activity was exhibited with R values ranging from 0.7580 to 0.8874 indicating a linear relationship The extracts phenolic composition was studied by HPLC. All extracts showed remarkable antioxidant activity (87 to 96%) while moderate activity was exhibited against protease (22 to 56%). Gallic acid, tannic acid, quercetin, rutin, catechin, hesperidin, and cinnamic acid were identified as the major phenolic acids in the extracts of selected medicinal plants.